2000
DOI: 10.1111/j.1749-6632.2000.tb06703.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of Representational Difference Analysis and cDNA Arrays for Transcriptional Profiling of Tumor Tissue

Abstract: Representational difference analysis of cDNA (cDNA‐RDA) was used for a comparison of the global transcript level of tumor of the larynx and the corresponding normal epithelial tissue toward the end of detecting differentially expressed genes. Overall, some 130 gene fragments were identified. By sequence analysis and homology comparison, they could be put into several groups related to (potential) functions. Apart from genes whose overexpression was most likely a result of tumor growth or dedifferentiation of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…rs16901966 (region 2), rs11986220 (region 1) at 8q24 on chromosome 8 were verified to have consistent associations in various populations [ 18 , 27 , 33 , 34 , 35 ]. rs1983891 is located in FOXP4, which belongs to subfamily P of the forkhead box (FOX) transcription factor family, and is associated with kidney tumors, larynx carcinoma, and breast tumors [ 36 , 37 , 38 ]. At present, the potential role for FOXP4 in prostate tumorigenesis has not been determined.…”
Section: Discussionmentioning
confidence: 99%
“…rs16901966 (region 2), rs11986220 (region 1) at 8q24 on chromosome 8 were verified to have consistent associations in various populations [ 18 , 27 , 33 , 34 , 35 ]. rs1983891 is located in FOXP4, which belongs to subfamily P of the forkhead box (FOX) transcription factor family, and is associated with kidney tumors, larynx carcinoma, and breast tumors [ 36 , 37 , 38 ]. At present, the potential role for FOXP4 in prostate tumorigenesis has not been determined.…”
Section: Discussionmentioning
confidence: 99%
“…Its advantages and limitations are well known [Hubank and Schatz, 1999;Chang, 2002]. Before DNA arrays were widely available, several labs used RDA to generate a library of clones that were subsequently arrayed onto nylon membranes and used for comparisons of normal and tumor tissues Welford et al, 1998;Frohme et al, 2000;Ismail et al, 2000]. For our purposes, RDA was attractive because target sequences are amplified by PCR with universal adapters annealed to every one of the digested fragments of DNA.…”
Section: Gene Expression and Discovery By Rdamentioning
confidence: 99%
“…Contrary to DDRT-PCR analysis, the cDNA-RDA method was infrequently used in plant functional genomics. Nevertheless, there are numerous positive reports from human genomics (Frohme et al, 2000;Yoon et al, 2001;Simkhovich et al, 2003) and rare examples from plants The increased tester-to-driver ratios are indicated. dp1, Homogeneous product of Karat/rhl1.a root transcriptome differentiation.…”
mentioning
confidence: 99%